The legal study on forestry law in Peninsular Malaysia: a special focus on the Permanent Reserved Forest (PRF) title / Ezuria Shahri … [et al.] - Shahri, Ezuria; Zubir, Nur Diyana; Zainal, Nur Amalina; Rusnan, Mohd Affifuddin (2014)
This study was conducted to examine the laws regulating the Permanent Reserved Forest (PRF) in Selangor, Perak and Negeri Sembilan. The focus is on the gazette and degazettement of PRF's title. This is a qualitative research where the data and information were obtained through the method of collecting data and relevant materials from various sources. Interviews were also conducted on a number of experts such as academician, government officials and also non-governmental organizations. The legislation that governs the PRF falls under the National Forestry Act 1984. The Acts provides a way for forest to be gazetted as PRF. However, there is a provision that allows the PRF to be degazetted if the State Authority is satisfied. There is no 'check and balance'. It is concluded that the protection of permanent reserved forest is not that strict as the title is easily being stripped off, with the exception in Selangor, where Selangor is the only state that practices public participation before degazettement of permanent reserved forest.